The Relationship Between Parenting Styles And Student Discipline Behavior In Physical Education And Health Learning In Upper-Grade Class Elementary School - Rozaq, Arsyad Finarkhan; Safari, Indra; Rahman, Aam Ali (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the relationship between Parenting and Student Disciplinary Behavior in Learning Physical Education, Sports, and Health (PJOK) in high grades in elementary schools. Using a Quantitative approach with a Correlational method that aims to determine the relationship between two variables. Data were collected through instruments in the form of questionnaire sheets of parental parenting patterns and questionnaire sheets of student discipline in the subject (PJOK) as part of a survey research design filled out by 4th, 5th, and 6th-grade students in elementary schools selected as research samples from elementary schools in Cimanggung District. In this study, the sampling used the Total Sampling technique. The sample of this study amounted to 124 students using the SPSS version.26 software for Windows. Analyzing data using correlation through the stages of normality and linearity test, Kolmogorov-Smirnov, and performing the Pearson correlation test. The results showed that there is a significant and positive relationship between parenting patterns and students' disciplinary behaviour in the context of learning Physical Education, Sports and Health (PJOK) in high school classes. The analysis results produced a correlation coefficient (r) of 0.375 with a very low significance level (p) of 0.002. This significance level (p) of 0.002 is far below the conventional significance threshold set at 0.05. The implication of this study confirms that teachers and parents have a crucial role in creating a supportive learning environment that is responsive to students' disciplinary behaviour. Therefore, effective communication strategies, more adaptive learning approaches, as well as support from schools and parents, are important elements in improving their disciplinary behaviour during physical education learning.